Three Days Extensive Survey of Malaria, Dengue and Chikungunya Mosquitoes in The Capital of Rajasthan, India: Life Science-Entomology - Prasad, Arti; Kumar, Devendra; Kumar, Ashok; Dev Jakhar, Saha; Kumar Kumawat, Ajay (International Journal of Life Science and Pharma Research, 2022)
The mosquito-borne diseases are transmitted among people by the bite of an infected mosquito. In India, the major mosquito vectors belong to three genera Aedes, Anopheles and Culex. The mosquito-borne disease transmission dynamics is ruled by a series of various type of factors like changes in climatic conditions, and other man-made factors like different types of land use, community hygiene and their behaviors etc. The presence of mosquitoes is a major concern for public health due to possibility of transmitting arboviral diseases like malaria, dengue and chikungunya; which repeatedly occurs in India and cause substantial morbidity and mortality annually. Current study was carried out in Jaipur district to determine the larval density, breeding preference and relative abundance of Anopheline and Aedes mosquitoes during October month of 2021 because there is less information available regarding vector breeding preference and other associated factors in surveyed areas. Survey was carried out in various place of Jaipur district [Chand Pole, Chhoti Chopad, Mahal Road, Jagatpura and Chaksu (Kothun)]. Total 185 houses were surveyed, among them 140 houses were found positive for Aedes and Anopheline mosquitoes. The larval indices like House Index (HI), Container Index (CI), Breteau Index (BI) and Pupae Index (PI) were calculated as 75.67%, 46.89%, 142.70 and 25.94 respectively. Total 46.89% of inspected containers were found positive for mosquitoes’ immature stages. The cattle drinking tanks were found as the most suitable breeding container with 82.75% positivity. This study concludes that Aedes aegypti, Aedes albopictus and Anopheles stephensi was found as the most abundant mosquito in this region so this area at high risk for mosquito-borne disease. The study recommends that the surveillance program regarding vector ecology and biology should be carried out in this area and an awareness program should be also conducted regarding vector and their breeding preferences